The role of follicular fluid and serum kisspeptin in infertile women with polycystic ovary syndrome and poor responders undergoing IVF/ICSI - Aydin, S.; Celik, N.; Acet, M.; Yardim, M.; Kenanoglu, O.; Acet, T.; Celik, O. (Wiley-Blackwell, 2016)
[Abstract Not Available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY